Implementation of Value Added Tax (VAT) Tax Planning in Service Companies: A Study - Dwi Fionasari; Barnard Putra; Fajar; Khahlil Gibran; Afdal Andika (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2025)
Value Added Tax (VAT) poses unique cash flow challenges for service companies in Indonesia because the obligation to collect it arises upon delivery of the service, regardless of receipt of payment. This study analyzes the implementation of VAT tax planning at PT DNG, a plantation services company, within the context of the Coretax Administration System. Using a qualitative case study approach, purposive sampling targeted two key informants (the Head of Finance and the Tax Officer). Semi-structured interviews and documentation served as the primary instruments, analyzed using the Miles and Huberman interactive model. The results indicate that PT DNG's VAT tax planning is effective, focusing on compliance and controlling administrative risks, supported by Coretax's automated calculation and reporting features. However, structural cash flow pressures persist due to 30-60 day delays in customer payments against timely deposit obligations. The conclusions emphasize that integrating tax planning with accounts receivable management exceeds the capabilities of a digital system alone.